Immune-metabolic mechanisms of post-traumatic stress disorder and atherosclerosis - Tian, Yali; Ullah, Hanif; Gu, Jun; Li, Ka (Frontiers in Physiology, 2023)
The interaction of post-traumatic stress disorder (PTSD) and atherosclerosis (AS) increase the risk of mortality. Metabolism and immunity play important roles in the comorbidity associated with PTSD and AS. The adenosine monophosphate-activated protein kinase/mammalian target of rapamycin and phosphatidylinositol 3-kinase/Akt pathways are attractive research topics in the fields of metabolism, immunity, and autophagy. They may be effective intervention targets in the prevention and treatment of PTSD comorbidity with AS. Herein, we comprehensively review metabolic factors, including glutamate and lipid alterations, in PTSD comorbidity with AS and discuss the possible implications in the pathophysiology of the diseases.